Tomographic diagnosis of adrenal tuberculosis and addison - height - Tinoco Solorzano, Juan Amilcar (2020)
We report the case of a 23-year-old male, natural and resident of height, with hyperpigmentation. Asthenia, fatigue, nausea, vomiting, weight loss, abdominal pain, hiporexia and hypotension, with decreased cortisol dosage and elevated ACTH.  Normal chest X-Ray, smear in sputum and negative urine. Negative TB-LAM Antigen. In contrasted abdomen computed tomography, an increase in dimensions and small calcifications is shown in both adrenals suggestive of specific type granulomatous infiltration. In endemic areas of tuberculosis as in Peru, in the absence of the adrenal biopsy, it can be used early, as a diagnostic alternative to the tomography to rule out the adrenal commitment.  In conclusion, this report described as the tomography can be used as an alternative diagnostic method in hospitals where it is not feasible to perform the biopsy in a rapid manner.